Modification of titanium orthopedic implants with bioactive glass: a systematic review of in vivo and in vitro studies - Liang, Jin; Lu, XinYue; Zheng, XinRu; Li, Yu Ru; Geng, XiaoYu; Sun, KeXin; Cai, HongXin; Jia, Qi; Jiang, Heng Bo; Liu, Kai (Frontiers in Bioengineering and Biotechnology, 2023)
Bioactive glasses are ideal biomaterial in the field of bio-restoration due to their excellent biocompatibility. Titanium alloy is widely used as a bone graft substitute material because of its excellent corrosion resistance and mechanical properties; however, its biological inertness makes it prone to failure clinically. Surface modification of titanium alloys with bioactive glass can effectively combine the superior mechanical properties of the substrate with the biological properties of the coating material. In this review, the relevant articles published from 2013 to present in four databases, Web of Science, PubMed, Embase, and Scopus were searched and after the screening, 49 studies were included. We systematically reviewed the basic information and the study types of the included studies, which are in-vitro experiments, animal tests, and clinical trials. In addition, we summarized the applied coating technologies including pulsed laser deposition, electrophoretic deposition, dip coating, and magnetron sputtering deposition. The superior biocompatibility of the materials in terms of cytotoxicity, cell activity, hemocompatibility, anti-inflammatory properties, bioactivity, and their good bioactivity in terms of osseointegration, osteogenesis, angiogenesis, and soft tissue adhesion were discussed. We also analyzed the advantages of the existing materials and the prospects for further research. Even though the current research status is not extensive enough, it is still believed that BG-coated Ti implants have great clinical application prospects.